2022
DOI: 10.3389/feart.2022.852742
|View full text |Cite
|
Sign up to set email alerts
|

How Aseismic Ridges Modify the Dynamics of Free Subduction: A 3-D Numerical Investigation

Abstract: The subduction of positively buoyant features has been implicated in the development of flat and shallow dipping slabs, the formation of cusps in trench geometry, and the cessation of associated arc magmatism. However, how such buoyant anomalies influence subduction dynamics to produce these different tectonic expressions remains debated. In this paper, using a series of multi-material 3-D simulations of free subduction, we investigate how linear buoyant ridges modify subduction dynamics, in particular downgoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 111 publications
1
17
0
Order By: Relevance
“…Interactions with nearby past or ongoing subduction zones may also affect the sinking velocity and slab penetration of the mantle transition zone (e.g., Becker & Faccenna, 2011; Čížková & Bina, 2019; Fukao & Obayashi, 2013; Fukao et al., 2009). The subduction of locally thickened oceanic lithosphere, such as oceanic plateaus, aseismic ridges or seamount chains, has been proposed to influence the shape of the trench and change the geometry of subducting slabs (e.g., Capitanio et al., 2011; Cross & Pilger, 1982; Gutscher, Malavieille, et al., 1999; Martinod et al., 2005; Suchoy et al., 2022). The higher compositional buoyancy of oceanic plateaus and ridges could resist slab sinking into the mantle and, thus, potentially lead to flat slab subduction (e.g., Mason et al., 2010; van Hunen et al., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Interactions with nearby past or ongoing subduction zones may also affect the sinking velocity and slab penetration of the mantle transition zone (e.g., Becker & Faccenna, 2011; Čížková & Bina, 2019; Fukao & Obayashi, 2013; Fukao et al., 2009). The subduction of locally thickened oceanic lithosphere, such as oceanic plateaus, aseismic ridges or seamount chains, has been proposed to influence the shape of the trench and change the geometry of subducting slabs (e.g., Capitanio et al., 2011; Cross & Pilger, 1982; Gutscher, Malavieille, et al., 1999; Martinod et al., 2005; Suchoy et al., 2022). The higher compositional buoyancy of oceanic plateaus and ridges could resist slab sinking into the mantle and, thus, potentially lead to flat slab subduction (e.g., Mason et al., 2010; van Hunen et al., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Interactions with nearby past or ongoing subduction zones may also affect the sinking velocity and slab penetration of the mantle transition zone (e.g., Fukao et al, 2009;Becker & Faccenna, 2011;Fukao & Obayashi, 2013b;Čížková & Bina, 2019). The subduction of locally thickened oceanic lithosphere, such as oceanic plateaus, aseismic ridges or seamount chains, has been proposed to influence the shape of the trench and change the geometry of subducting slabs (e.g., Cross & Pilger, 1982;Gutscher, Malavieille, et al, 1999;Martinod et al, 2005;Capitanio et al, 2011;Suchoy et al, 2022). The higher compositional buoyancy of oceanic plateaus and ridges could resist slab sinking into the mantle and, thus, potentially lead to flat slab subduction (e.g., van Hunen et al, 2002;Mason et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that trench motion is retarded in the vicinity of buoyant features, pinning the trench in a cusp shape (e.g., Mason et al, 2010;Suchoy et al, 2022). Suchoy et al (2022) investigated the subduction of buoyant anomalies with Cartesian numerical models using a similar setup to the C_W2400 case analyzed here, and found that their effect is dependent upon their location along the trench. When the buoyant ridge impinges at the center of the trench, where trench motion is already hindered by plate width, trench retreat is further reduced locally, leading to significant along-strike variations in trench shape and locally reducing slab dip.…”
Section: Implications For the Spatial And Temporal Evolution Of Earth...mentioning
confidence: 93%
“…One example is how the presence of buoyant anomalies, such as oceanic plateaus and ridges, influence the evolution of subduction systems. Previous studies have found that trench motion is retarded in the vicinity of buoyant features, pinning the trench in a cusp shape (e.g., Mason et al, 2010;Suchoy et al, 2022). Suchoy et al (2022) investigated the subduction of buoyant anomalies with Cartesian numerical models using a similar setup to the C_W2400 case analyzed here, and found that their effect is dependent upon their location along the trench.…”
Section: Implications For the Spatial And Temporal Evolution Of Earth...mentioning
confidence: 93%
See 1 more Smart Citation